PENERAPAN THE LEARNING CELL DISERTAI KUIS UNTUK MENUMBUHKEMBANGKANKEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII MTsN LEMBAH GUMANTI - Rahm, Muthia; Rahmi, Rahmi; febriana, Rina (Pendidikan Matematika, 2014)
ABSTRAKThe research background by mathematis communications skills of students is still low and willingness of students to ask and express ideas in learning is low. The research to aim for to knowÂ  mathematis communications skills with apply The Learning Cell strategy with Quiz better then conventional learning and to know development mathematis communications skills of students with apply The Learning Cell strategy with Quiz student of class VIII MTsN Lembah Gumanti. This type of research is exsperimental research by design randomized trial on the subject. Population in the study were students of class VIII B and a control class VIII C. Instruments used in the study is quiz and final test in the form of essays. The type of the test is essay with reliabilitas 0,94. Hypotesis test to used t-test with MINITAB P-value 0,009 means less than a = 0,05, the hypothenical in this study received. So by applying The Leraning Cell strategy with Quiz better then by matematis communication skills of students with conventional learning student of VIII MTsN Lembah Gumanti.